Signatures of quantum effects on radiation reaction in laser–electron-beam collisions. (October 2017) - Ridgers, C. P.; Blackburn, T. G.; Del Sorbo, D.; Bradley, L. E.; Slade-Lowther, C.; Baird, C. D.; Mangles, S. P. D.; McKenna, P.; Marklund, M.; Murphy, C. D.; Thomas, A. G. R.
Abstract : Two signatures of quantum effects on radiation reaction in the collision of a GeV electron beam with a high intensity ( >3× 10^20 W cm^-2 ) laser pulse have been considered. We show that the decrease in the average energy of the electron beam may be used to measure the Gaunt factor g for synchrotron emission. We derive an equation for the evolution of the variance in the energy of the electron beam in the quantum regime, i.e. quantum efficiency parameter [STIX]x1D7021 . We show that the evolution of the variance may be used as a direct measure of the quantum stochasticity of the radiation reaction and determine the parameter regime where this is observable. For example, stochastic emission results in a 25 % increase in the standard deviation of the energy spectrum of a GeV electron beam, 1 fs after it collides with a laser pulse of intensity 10^21 W cm^-2 . This effect should therefore be measurable using current high-intensity laser systems.